Trade union density in Iceland - Aðalsteinsson, Gylfi Dalmann; Guðlaugsson, Þórhallur Örn (Stjórnsýslustofnun, 2019)
Few studies have been conducted on trade union density in Iceland, some has been written about trade unions in Iceland. There has been a lot of debate in Europe over the last 20 years of declining trade union density. There are various reasons for this decline, such as general economic prosperity since the end of the Second World War, EU directives and regulations on increased rights and protection of workers, more focus on work life balance, increased economic growth, higher employment rates, structural change in the labour market and new management practices that encourage employees to be outside of trade unions. Furthermore, as a possible explanation, internationalization and fierce competition of companies in global markets has also been pointed out, greater emphasis on flexibility in employment contracts, job outsourcing and the fact that it is more difficult to get well-educated professionals to be union members. The development of trade union density in Iceland has been different. For the last 20 years, trade union density in Iceland has been very high and remained fairly stable. This paper deals with trade union density in Iceland from 1994 to 2016. Few proposition, according to the authors’ assessment, are put forward that can shed light on high union density in Iceland. They are: 1) closed shop agreements, 2) check-off system, legal obligation for employers to deducts a portion of an employee’s wages to pay union dues, 3) large public sector, 4) strategic work of trade unions to make union membership attracting with various services and benefits for members, 5) trade unions has emphasized on reaching to young people in the labour market, 6) trade union membership granted union members access to pension fund, 7) the “Ghent system” which linked unemployment benefits to union membership. Fáar rannsóknir hafa verið gerðar á stéttarfélagsaðild hér á landi en nokkrar um stéttarfélög. Mikil umræða hefur verið í Evrópu síðustu 20 ár um minnkandi stéttarfélagsaðild en þar hefur dregið nokkuð úr aðild. Ýmsar ...